MODERN ART: INTEGRATING SOCIO-AFFECTIVE STRATEGY TO ENHANCE INDONESIAN AND THAI STUDENTS’ INTERACTION IN THE CLASSROOM - Wahyu Mustikasari, Rr. Dewi (Faculty of Education and Teacher Training, Universitas Islam Negeri Walisongo Semarang, 2015)
There were some obstacles which happened in my Writing 1classses due to the languages that were being used for communica-tion, and my Indonesian and Thai Students’ were not communica-tive to interact in the classroom. In this paper, I propose the inte-gratation of socio-affective strategy to boost my Indonesian andThai Students’ interaction that can be facilitated by using modertart. Modern art has several interesting points namely it may displaythe real-world activities, use communicative language, foster persua-sive communication, facilitate student to use their socio-affectivestrategy, and provide integrated skills.